Potential Mosquito Larvicides from Morinda citrifolia Root Extract - Ping, Wen Yin; Lian, Gwendeline Ee Cheng; Bong, J>C>F; Sukari, Mohad Aspollah (Malaysian Journal of Science, 2009)
In our recent investigation on Morinda citrifolia as a potential larvicide against the larvae of Aedes aegypti, we found 1-hydroxy-2-methyl anthraquinone (1) to have good larvicidal activity. Extracts of the roots of Morinda citrifolia were also found to be larvicidal.